Case report: Rare pulmonary fungal infection caused by Penicillium digitatum: the first clinical report in China - Shi, Xiaojuan; Ye, Jiaqing; Liu, Peiling; Gao, Weili; Feng, Zhongjun; Zheng, Cuiying; Huang, Yinqi; Guo, Yumei; Zhang, Lijie (Frontiers in Medicine, 2024)
Penicillium digitatum is a common plant pathogen that causes citrus rot, which is extremely rare in humans. We report a case of a 66-year-old man with a history of consuming large amounts of citrus fruit, smoking for 30 years, and a history of emphysema. He had experienced intermittent cough with sputum for more than 10 years, and was admitted to the hospital due to worsening symptoms for a month. Despite antibiotic treatment, the effect was poor. Subsequently, bronchoalveolar lavage fluid (BALF) was detected by metagenomic next-generation sequencing (mNGS), showing the presence of P. digitatum. The fungal culture of BALF also suggested the Penicillium genus. The diagnosis was P. digitatum lung infection, and the patient was treated with itraconazole and the lung infection was controlled. This is the third reported case of invasive pulmonary fungal infection caused by P. digitatum globally at the genus level and the first in China. Although human infections caused by P. digitatum are rare, as an emerging opportunistic pathogen, the detection of this fungus in immunocompromised patients should still be clinically important.